2019
DOI: 10.3390/nu11040719
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Meal Frequency and Timing on Health in Humans: The Role of Fasting

Abstract: The influence of meal frequency and timing on health and disease has been a topic of interest for many years. While epidemiological evidence indicates an association between higher meal frequencies and lower disease risk, experimental trials have shown conflicting results. Furthermore, recent prospective research has demonstrated a significant increase in disease risk with a high meal frequency (≥6 meals/day) as compared to a low meal frequency (1–2 meals/day). Apart from meal frequency and timing we also have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
232
2
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(262 citation statements)
references
References 119 publications
(150 reference statements)
6
232
2
22
Order By: Relevance
“…In addition, food consumption under unsynchronized circadian rhythm is bad for health and increases the risk of disease. In humans and mice, the energy consumption in the early phase of the active period with constant fasting time decreases inflammation, improves the circadian rhythm, increases the resistance to autophagy and stress, and controls the intestinal microbiota [52]. These papers have suggested that morning is a good time for production of a clear reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, food consumption under unsynchronized circadian rhythm is bad for health and increases the risk of disease. In humans and mice, the energy consumption in the early phase of the active period with constant fasting time decreases inflammation, improves the circadian rhythm, increases the resistance to autophagy and stress, and controls the intestinal microbiota [52]. These papers have suggested that morning is a good time for production of a clear reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Ogilvie RP et al reported that individuals who go to bed at 12:30 am or later tended to skip breakfast as compared with those who go to bed at 10:30 pm or earlier [28]. In addition, breakfast skipping has been reported to be associated with elevated serum LDL-C levels and increased body weight and body fat mass [29,30]. In the present study, the men who slept for ³8 h may have had late bedtimes, and bad eating habits could have been involved in the deterioration of the serum LDL-C and non-HDL-C levels and exacerbation of abdominal obesity in these men.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that skipping meals, especially breakfast, was associated with a higher prevalence of CMR factors [15][16][17], whereas a higher meal frequency was associated with a lower risk of obesity, high cholesterol, and diabetes in adults [18][19][20]. More recent research in adults has shown that three to four meals per day were associated with lower CMR, compared with one to two, or six or more meals per day [13]. Some studies have demonstrated that a late-night meal is associated with poorer diet quality and adiposity among adults [21,22].…”
mentioning
confidence: 98%
“…Moderate fat intake at lunch was associated with a lower increase in CMRS. Meal patterns driven by energy were not significantly associated with CMR factors; however, a low carbohydrate-high protein-moderate fat lunch and low carbohydrate-high protein dinner were associated with favorable changes in CMRS in children.Evidence from recent studies in adults has shown that meal patterns play an important role in the development of CMR factors [12,13]. Eating three meals (breakfast, lunch, and dinner) plus snacks per day is a norm and may be an optimal choice for health [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation